Alternative treatments for footwear industry liquid effluents part 1 - Pressure wet oxygen oxidation - Ferreira, MJ (2002)
Coagulation/flocculation followed by carbon adsorption may allow the discharge of the final effluent to sewage systems but the sludge produced and the adsorbent required makes the process of doubtful feasibility. Even with this treatment, threshold values for discharging the effluent to surface waters are not achieved. Such limitations encountered with these more conventional treatments pushed the research towards other less conventional options. One of them is wet oxidation (WO) here studied with oxygen as the selected oxidant. Thus, experiments were carried out to evaluate the influence of temperature, time, oxygen and pH on the reduction of effluent chemical oxygen demand (COD). In addition, the catalytic effect of copper sulphate on the WO treatment efficiency was evaluated. The WO treatment of these wastewaters using oxygen as oxidant requires at least 200 degreesC, 30 minutes and non-alkaline pH, preferably pH2. The catalytic effect of copper is only small thus its role is not of interest for this purpose.